2005
DOI: 10.1130/b25553.1
|View full text |Cite
|
Sign up to set email alerts
|

Using U-Pb ages of Miocene tufa for correlation in a terrestrial succession, Barstow Formation, California

Abstract: Sedimentary rocks and associated fossils are the direct record of past life and its environmental context. Few methods allow direct and precise dating of this important archive, making it diffi cult to correlate climate, biologic, and tectonic events preserved in terrestrial records. We sampled lacustrine tufa calcite from the middle member of the Miocene Barstow Formation to further test the feasibility of uranium-lead dating of terrestrial carbonates. Five samples yield U-Pb ages (2σ) of 14.81 ± 0.39 Ma, 15.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 48 publications
(49 reference statements)
1
19
0
Order By: Relevance
“…A sample from the base of Member B in the type section was analyzed by TIMS at Stony Brook University following the method of Cole et al (2005). The resulting errorchron age of 66.1 ± 5.4 Ma (MSWD = 34) corroborates earlier Maastrichtian to Paleocene fossil age assignments (Fouch, 1979;Good, 1987).…”
Section: U-pb Microbial Carbonate Datingmentioning
confidence: 90%
See 1 more Smart Citation
“…A sample from the base of Member B in the type section was analyzed by TIMS at Stony Brook University following the method of Cole et al (2005). The resulting errorchron age of 66.1 ± 5.4 Ma (MSWD = 34) corroborates earlier Maastrichtian to Paleocene fossil age assignments (Fouch, 1979;Good, 1987).…”
Section: U-pb Microbial Carbonate Datingmentioning
confidence: 90%
“…Recent studies of lacustrine carbonates have shown that calcite may contain elevated levels of uranium due to complexation with organic matter from sources such as microbial mats, and that U-Pb ages representing depositional ages may be determined by TIMS (Cole et al, 2005).…”
Section: U-pb Microbial Carbonate Datingmentioning
confidence: 99%
“…For example, in the youngest carbonate dated with U‐Pb, the age without considering U series disequilibrium was ∼25% younger than the corrected age [ Richards et al , 1998]. Disequilibrium expected in typical waters because of an absence of initial 230 Th would result in a change in the 238 U‐ 206 Pb age of −109 ka, and an initial 234 U/ 238 U activity ratio of 2 would result in a change of +354 ka [ Cole et al , 2005]. Thus, in older (Paleozoic and Mesozoic) deposits, any reasonable disequilibrium is likely accommodated within age uncertainties.…”
Section: Theoretical Basis Of U‐pb Geochronologymentioning
confidence: 99%
“…Some examples of carbonates that are formed by meteoric fluids that have been dated by U-Pb are cave deposits such as flowstones and stalagmites (Richards et al 1998;Polyak et al 2008;de Ruiter et al 2009;Cliff et al 2010;Pickering et al 2011;Woodhead et al 2012;Woodhead and Pickering 2012;Bajo et al 2012;Pickering et al 2013) and paleosol (fossil soil) carbonates such as nodules and rhizoliths (Hoff et al 1995;Winter and Johnson 1995;Rasbury et al 1997;Wang et al 1998;Leeder et al 2008;Ludvigson et al 2010). Lacustrine (lake) carbonates have also been shown to have good potential for U-Pb dating (Cole et al 2005;Druschke et al 2009). …”
Section: U-pb Dating Of the Fluids Of Diagenesismentioning
confidence: 95%